Subosukawonosraten Eco-Warehouse - Febrianto, Rizky Inar; , Dr. Ir. Qomarun, MM; , Ms.Priyono Nugroho, ST, MT (2016)
Subosukawonosraten Eco-Warehouse is a warehouse area of environmentally friendly flagship store manufactured goods from Surakarta, Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen and Klaten in the number and time frames which are then distributed to the intended location based on market demand. Besides, in an effort to design regional warehousing industry friendly environment by reducing waste and pollution, efficiently share resources (such as materials, water, energy, infrastructure, and natural resources) and help achieve sustainable development, with the aim of increasing the economic benefits and increases environmental quality. The Indonesian economy is weak and needs of industrial land, especially warehousing Limited makes the area Subosukawonosraten create a Forum Economic Development Region (FPEW) which aims to accommodate the superior products SMEs thus launched a program of One Village One Product (OVOP), excellent products is the need a storage facility as well as promotions to be distributed throughout Indonesia. Surakarta is a storefront commercial city and its strategic position amid Subosukawonosraten region into consideration in the design of the site selection. Expected by the Subosukawonosraten Eco-Warehouse can improve economic conditions in Indonesia through product development of SMEs by providing warehousing facilities, increasing the potential Surakarta as the City of Commerce, in cooperation with the district area Subosukawonosraten, resolve land issues given the need for land for industrial applications, especially warehousing in the Spatial Plan increasingly cramped for sustainable rice cultivation land requirement, and optimization capabilities warehousing area managers in the management services industry more environmentally friendly.